From Motivation to Identity: The Mediating Effect of Science Learning Self-efficacy - Rochelle C. Gabaleño; Yien Philicity L. Padernos; Albert Andry E. Panergayo; Lorelyn C. Rescober (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2026)
The Philippines consistently ranked bottom among different countries in international large-scale assessments. This stems from traditional teaching and lack of real-world application, affecting student engagement in science. Beyond structural reforms, students' long-term engagement in science may be increased by targeting these affective factors: science motivation (SM), science identity (SI), and science self-efficacy (SSE). Thus, this study investigated the Grade 10 students’ level among three variables and examined the influence of science motivation on students’ science identity, focusing on the mediating role of science self-efficacy. A descriptive correlational research design was utilized, and data were gathered from a random sample of 200 students using three adapted survey questionnaires: Science Motivation Questionnaire II, Students’ Science Identity Questionnaire, and Science Self-efficacy Scale. Mean and standard deviation uncovered that student’s level of SM, SI, and SSE are all high. Path analysis shows that the three variables have a strong positive predictive relationship. Mediation analysis further revealed that about 33.5% of the total effect is mediated by SSE, while 66.5% shows direct effect of SM to SI. The study found that SSE partially mediates the relationship between SM and SI, indicating that while motivation directly influence science identity, an increase in self-efficacy could further strengthen this connection. Teachers can enhance students’ science motivation and self-efficacy by incorporate hands-on activities, real-world applications, and success in scientific tasks, which increase their science identity.